Clinical outcome of intentional replantation with preoperative orthodontic extrusion: a retrospective study. (19th March 2014) - Choi, Y. H.; Bae, J. H.; Kim, Y. K.; Kim, H. Y.; Kim, S. K.; Cho, B. H.
Abstract Aim To evaluate retrospectively the clinical outcomes of intentional replantation (IR) of teeth in terms of tooth survival and periradicular healing and to investigate their prognostic factors. Methodology Two hundred and eighty‐seven teeth treated by IR were analysed retrospectively. Clinical outcomes between the cases with preoperative orthodontic extrusion for 2–3 week and those without extrusion were analysed. The outcomes of IR were determined by clinical and radiographic evaluation. Tooth survival and periradicular healing estimates were compared using Kaplan–Meier analysis. The contribution of a patient's age and gender, tooth type and location, and preoperative orthodontic extrusion was investigated using the multivariate Cox proportional hazard model. Results The mean follow‐up period was 25.4 ± 9.3 months. The overall success rate of IR was 89.5% based on periradicular healing. The overall survival rate was 95.1%. The survival rates were 91.2% for the teeth extracted without extrusion and 98.1% for those extracted with extrusion. Amongst the variables tested, only the extraction technique with preoperative orthodontic extrusion significantly affected the survival rate (P = 0.016). Other prognostic variables, such as age and gender, tooth type and location, did not affect the survival of intentionally replanted teeth. Conclusions Intentional replantation was a viable treatment option for teeth with previously failed nonsurgical root canal treatment, regardless of a patient's age and gender, and tooth type and location. Preoperative orthodontic extrusion for 2–3 weeks reduced root resorption and tooth fracture and can be recommended to enhance the outcome of IR.